Characterization of dielectric relaxation, electrical conductivity and impedance spectroscopy of lead-free Li0.5Bi0.5Ti0.8Zr0.2O3 ceramic. Issue 1 (29th March 2022) - Panda, D.; Sahoo, P. S.; Mohanty, B. B.; Mishra, L. K.; Behera, S. K.; Choudhary, R. N. P.
Abstract: This article focuses on dielectric, electrical, and impedance spectroscopy analysis of lead-free ceramic Zr modified Lithium Bismuth Titanate (Li0.5 Bi0.5 Ti0.8 Zr0.2 O3 ), possessing orthorhombic structure prepared by high-temperature mixed oxide method. The room temperature X-ray diffraction study confirms the formation of a single-phase orthorhombic compound. SEM micrograph shows the homogenous and non-uniform distribution of the grains with grain size 4.9 μm. The dielectric, electrical, and impedance properties of the compound are investigated in a broad frequency (10 3 −10 6 Hz) and temperature (33 °C–500 °C) range. Dielectric anomaly is observed at 112 °C showing phase transition from ferroelectric to paraelectric state and the maximum value of the dielectric constant is nearly 225 at 10 kHz. Fitted Nyquist plots show the involvement of both bulk and bulk interface to the relaxation processes. The temperature-dependent ac conductivity informs the nature of the variation of conductivity and activation energy in various zones. The impedance loss spectra show the fall in resistance with a rise in temperature which confirms the negative temperature coefficient of resistance (NTCR) nature of the compound. Complex modulus Cole-Cole plots suggest that the presence of a non-Debye type relaxation process which is poly dispersive and in nature.